Foreign Direct Investment in Chile: Historical Process, changing political ideologies and the responses of MNEs (2019)
The objective of this paper is to identify how historical process and changing political ideologies have affected the responses of MNEs to investment in Chile. Using the historical dimension we provide a trajectory of development along which the Chilean economic system influenced by shifts in political ideologies has evolved. For each section we categorized the responses of MNEs during these periods of investment. We then offer some contributions to theory and implications for managers by suggesting that understanding the functioning of a political system assists firm to develop and execute appropriate risk management strategies.